Marathon related cardiac arrest risk differences in men and women - Roberts, W. O.; Roberts, D. M.; Lunos, S. (British Journal of Sports Medicine, 2013)
Objective: To determine the incidence of sudden cardiac arrest (SCA) and sudden cardiac death (SCD) in men and women.Design Retrospective cohort study. Setting: Two popular urban 42 km marathons.Participants 1982 to 2009 finishers. Assessment of risk factors: Race records were assessed for finishers, age distribution and cardiac events by sex. Main outcome measures: The SCA/SCD incidence for all (total), male and female finishers. Results There were 548 092 finishers with women finishers increasing from 10% to 40% over the first 18 years and remaining near 40% for the last decade. There were 14 SCA events (1 woman, 13 men) with seven successful resuscitations yielding an all finishers SCA rate of 2.6 per 100 000 finishers. The SCA rates (per 100 000) for men and women were 3.4 (95% CI: 1.8 to 5.9) and 0.6 (95% CI: 0.0 to 3.3), respectively (p=0.079). The male SCA rate for the 2000-2009 decade was 4.6 per 100 000 finishers (95% CI: 1.8 to 9.5). Eleven of 13 men were >39 years old. The OR of a man experiencing SCA compared with woman was 5.7. Conclusions: As the number of women participating in these two marathons has increased, the difference between the men's and total SCA and SCD incidence has increased for men, especially >39 years old, from coronary artery disease with men's incidence for SCA of 1 in 22 000 and SCD at 1 in 50 000 finishers over past decade.